The final judgment - Patterson, Richard North (New York : St. Martin's Paperbacks, 2011)
Defense attorney Caroline Masters is called upon to defend her niece who has been accused of murder, forcing her to deal with old memories and family members she had swept from her life when she left home over twenty years earlier.
Kirkus Review
Wilson's Fiction
Kirkus Review, October 1995
Wilson's Fiction, October 2010
Adult.
Adult
Keywords: Families -- New Hampshire -- Fiction; Trials (Murder) -- New Hampshire -- Fiction; Women lawyers -- New Hampshire -- Fiction; Family life -- New Hampshire -- Fiction; Legal stories; Trials (Homicide) -- Fiction; Women lawyers -- Fiction; Legal stories